The galerucinae from Sarawak (Coleoptera: Chrysomelidae) - Mohamed S. Mohamed Said, (Universiti Kebangsaan Malaysia, 1999)
The present study on the chrysomelid beetles of the subfamily Galerucinae from Sarawak has recorded an impressive number of species. There are 181 species, in 53 genera, greatly increased from the previous records. 38% of the total species are represented by single specimens. The four most widely distributed species are Monolepta impressicollis Jacoby, Theopea elegantula Baly, Mimastra sumatrensis Jacoby and Monolepta marginicollis Jacoby. The Galerucinae are distributed unevenly in all localities surveyed, with nearly 75% of the species restricted to one locality, and the other 25% shared with at least two localities. The distribution pattern of the Galerucinae shows many facets of vegetation in the rainforest of Sarawak. The gazetting of the proposed areas that have been identified as new National Parks and Wildlife Sanctuaries is most welcome.